Using social and mobile tools for weight loss in overweight and obese young adults (Project SMART): a 2 year, parallel-group, randomised, controlled trial. Issue 9 (September 2016) - Godino, Job G; Merchant, Gina; Norman, Gregory J; Donohue, Michael C; Marshall, Simon J; Fowler, James H; Calfas, Karen J; Huang, Jeannie S; Rock, Cheryl L; Griswold, William G; Gupta, Anjali; Raab, Fredric; et al.
Summary: Background: Few weight loss interventions are evaluated for longer than a year, and even fewer employ social and mobile technologies commonly used among young adults. We assessed the efficacy of a 2 year, theory-based, weight loss intervention that was remotely and adaptively delivered via integrated user experiences with Facebook, mobile apps, text messaging, emails, a website, and technology-mediated communication with a health coach (the SMART intervention). Methods: In this parallel-group, randomised, controlled trial, we enrolled overweight or obese college students (aged 18–35 years) from three universities in San Diego, CA, USA. Participants were randomly assigned (1:1) to receive either the intervention (SMART intervention group) or general information about health and wellness (control group). We used computer-based permuted-block randomisation with block sizes of four, stratified by sex, ethnicity, and college. Participants, study staff, and investigators were masked until the intervention was assigned. The primary outcome was objectively measured weight in kg at 24 months. Differences between groups were evaluated using linear mixed-effects regression within an intention-to-treat framework. Objectively measured weight at 6, 12, and 18 months was included as a secondary outcome. The trial is registered with ClinicalTrials.gov, number NCT01200459 . Findings: Between May 18, 2011, and May 17, 2012, 404 individuals were randomly assigned to the intervention (n=202) or control (n=202). Participants' mean (SD) age was 22·7 (3·8) years. 284 (70%) participants were female and 125 (31%) were Hispanic. Mean (SD) body-mass index at baseline was 29·0 (2·8) kg/m 2 . At 24 months, weight was assessed in 341 (84%) participants, but all 404 were included in analyses. Weight, adjusted for sex, ethnicity, and college, was not significantly different between the groups at 24 months (−0·79 kg [95% CI −2·02 to 0·43], p=0·204). However, weight was significantly less in the intervention group compared with the control group at 6 months (−1·33 kg [95% CI −2·36 to −0·30], p=0·011) and 12 months (−1·33 kg [–2·30 to −0·35], p=0·008), but not 18 months (−0·67 kg [95% CI −1·69 to 0·35], p=0·200). One serious adverse event in the intervention group (gallstones) could be attributable to rapid and excessive weight loss. Interpretation: Social and mobile technologies did not facilitate sustained reductions in weight among young adults, although these approaches might facilitate limited short-term weight loss. Funding: The National Heart, Lung, and Blood Institute of the National Institutes of Health (U01 HL096715).